Pendampingan dalam Program Infrastruktur Sosial Ekonomi Wilayah (PISEW) di Kecamatan Lantari Jaya - Algiffari, M. Fauzhan (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Poverty is a challenge for the government that must be resolved in order to improve the economy in the region. The delay in the development of poor areas coupled with the global economic slowdown is very worrying, so instructions from the government are needed in improving infrastructure for basic settlement infrastructure that can create jobs for the community so that the community's economy increases. On December 10, 2019, the President of the Republic of Indonesia, at a meeting to direct the acceleration of the implementation of the infrastructure program, secured the Ministry of Public Works and Public Housing in increasing labor-intensive activities that intersect with empowering local communities so that they become a binding force for the economy. The Regional Economic Infrastructure Program (PISEW) in its journey is one of the government programs whose goal is to improve the community's economy using the self-management method which will be managed by community groups under the auspices of the Inter-Village Cooperation Agency (BKAD), so that the impact and benefits can be felt directly by the local community. This economic improvement is specifically for people who live in Lantari Jaya sub-district, Bombana district, Southeast Sulawesi province. In practice, community self-management is the direct manager, therefore assistance is needed and having competent assistants in determining and analyzing the infrastructure to be built, in order to improve the economy of the community.